Sistem Pendukung Keputusan Seleksi Atlet Pon Cabang Pencak Silat Menerapkan MOOSRA - Fitri Meilida (Bulletin of Computer Science Research, 2021)
Selection of pencak silat athletes at IPSI Deli Serdang is used to determine athletes who qualify to enter PON. Those who have good strength and technique in accordance with the criteria determined by IPSI Deli Serdang, so that athletes can be selected to enter the PON athletes in the pencak silat branch. The selection system for pencak silat athletes carried out in this research uses the Multi-Objective Optimization method on the basis of simple Ratio Analysis (MOOSRA). The MOOSRA method is used to calculate the criteria and weight values that have been determined by IPSI Deli Serdang to rank alternative pencak silat athletes.